PENGUATAN KELEMBAGAAN SD ISLAM MELALUI PENDANAAN ZIS DAN WAKAF BERBASIS PARTISIPASI UMAT DIGITAL UNTUK MEWUJUDKAN KEMANDIRIAN BIAYA OPERASIONAL SD DI KECAMATAN JAGAKARSA - Daffa Akmal, Mochamad; Suarni, Fitrima; Kasronudin; Rahman, Hasan Basri; Sulaiman, Suhendar; Bariyah, Oneng Nurul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to formulate a model for strengthening zakat, infaq, alms, and waqf (ZIS-Waqf) funds based on digital community participation to achieve operational financial independence of Islamic Elementary Schools (SDI) in Jagakarsa District. The background of this research is based on the low contribution of ZIS-Waqf funds to school operational costs, which is only around 5%, despite the significant potential of Islamic philanthropy within the community. This research employed a descriptive qualitative approach with a case study method involving five Islamic elementary schools in Jagakarsa District: SDI Al-Falah, SDI Al-Ikhlas, SDI Baitul Makmur, SDI Assalam, and SDI Nurul Iman. Data were collected through observation, interviews, and documentation. The findings reveal that the five schools possess strong social capital, including teacher loyalty, public trust, alumni networks, and active parent participation. However, the management of ZIS-Waqf funds remains suboptimal due to the absence of transparent and integrated digital systems. Based on these findings, this study proposes the “SAW-DIGI SDI” model consisting of four components: Easy, Reporting, Productive, and Affection. The model integrates QRIS-based payment systems, digital financial reporting, productive waqf development, and emotional engagement with donors. The implementation strategy is adjusted to the characteristics of each school. This study concludes that strengthening digital-based ZIS-Waqf participation has the potential to increase internal school financing contributions up to 30% of operational costs in a sustainable manner. Keywords: Digital ZIS-Waqf, School Financial Independence, Community Participation